The Effect of NIMA Matching in Adult Unrelated Mismatched Hematopoietic Stem Cell Transplantation – A Joint Study of the Acute Leukemia Working Party of the EBMT and the CIBMTR. - Pingel, Julia (Bone Marrow Transplant, 2018)
Hematological malignancies can be cured by unrelated donor allogeneic HSCT and outcomes are optimized by high resolution HLA matching at HLA-A, -B, -C, -DRB1 and -DQB1 (10/10 match). If a 10/10 match is unavailable, 9/10 matches may be suitable. Fetal exposure to non-inherited maternal antigens (NIMA) may impart lifelong NIMA tolerance modulating the immune response, as shown in adult haploidentical transplantation. In cord blood transplantation, NIMA matching lowered rates of aGvHD and TRM; in haploidentical transplantation, sibling donors with non-shared maternal antigens showed less grade II-IV aGvHD. This retrospective analysis examined if 9/10 matched unrelated donor HSCT benefits from NIMA matching. DKMS contacted 1,735 donors and obtained 733 (42%) maternal samples. NIMA-matched and -mismatched cases with a minimum follow-up of one year were compared by univariate and multivariate analyses adjusted for co-variates for OS, DFS, relapse, TRM and a/cGvHD. The study population (N=445) comprised 31 NIMA-matched and 414 NIMA-mismatched cases. No significant differences between NIMA-matched and -mismatched groups were found for any outcomes with similar OS and TRM rates within both groups. This study provides the proof of principle that NIMA matching is possible in the unrelated donor HSCT setting; larger studies may be able to provide significant results.